1981
DOI: 10.1063/1.92497
|View full text |Cite
|
Sign up to set email alerts
|

A large linear electro-optic effect in a polar organic crystal 2-methyl-4-nitroaniline

Abstract: The dc linear electro-optic effect and the x-ray crystal structure of the organic molecular solid 2-methyl-4-nitroaniline (MNA) have been studied. One polar orientation was found to have an exceptionally large figure of merit for electro-optic phase retardation ( 1/2 (n13r11−n33r31) = 270±50×10−12 m/V), which is traced to a single, large component of the corresponding microscopic molecular susceptibility. Comparison with second-harmonic generation data demonstrates that the liner electro-optic effect in MNA is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…It should be noted that different studies ,,,, have used different directions for MNA molecule, but all of them agree that d 33 = (1/2)­χ zzz (when the long molecular axis tends to be along the z -axis) is the dominant component. As pointed out by Levin et al, d 33 is phase matchable using the usual index birefringence and has the enormous figure of merit of 2000 times larger than LiNbO 3 .…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…It should be noted that different studies ,,,, have used different directions for MNA molecule, but all of them agree that d 33 = (1/2)­χ zzz (when the long molecular axis tends to be along the z -axis) is the dominant component. As pointed out by Levin et al, d 33 is phase matchable using the usual index birefringence and has the enormous figure of merit of 2000 times larger than LiNbO 3 .…”
Section: Resultsmentioning
confidence: 91%
“…Contrary to 2-amino-4-nitroaniline (for brevity, we name it ANA), the 2-methyl-4-nitroaniline (MNA) crystal has attracted much attention in different studies. The linear and nonlinear optical properties of MNA have already been the topic of several experimental and theoretical studies. The FT-IR spectra of crystalline MNA deposited on a poly substrate were studied by Vallee and co-workers. , Nogueira et al reported the longitudinal optical (LO) and transversal optical (TO) wavenumbers of polar vibrations found in the unpolarized FT-IR reflectivity spectra of MNA crystals.…”
Section: Introductionmentioning
confidence: 99%
“…Typically for polymers, is about three times larger than . At the current time, for most of the reported modulators, values range between 1-20 pm/V, although values as high as 67 pm/V have been reported [89]. The index change for an applied electric field is given by (10).…”
Section: ) Polymer Traveling-wave Modulatorsmentioning
confidence: 95%
“…Organic molecular crystals are attractive candidates for such materials, as well-established methods of synthetic chemistry enable almost continuous modification of NLO properties. Certain classes of organic materials, especially those with highly delocalized π electrons and additional donor/acceptor groups at opposite ends of the molecule, exhibit extremely large NLO effects, and many organic NLO crystals exhibit high optical damage thresholds, making them attractive in high-power applications. Properties of 2-methyl-4-nitroaniline (MNA), especially in the solid state, have been the focus of a large number of investigations since the late 1970s, when it was discovered that crystals of this compound exhibited an exceptionally large second-order optical nonlinearity and linear electrooptic effect, and interest in MNA and related molecules has remained strong because their unique properties promise potentially important applications.…”
Section: Introductionmentioning
confidence: 99%